2006
DOI: 10.1093/ndt/gfl356
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-carnitine infusions on inflammatory and nutritional markers in haemodialysis patients

Abstract: There was a significant benefit of L-carnitine on CRP, transferrin, total protein and albumin levels of the haemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 17 publications
3
61
0
1
Order By: Relevance
“…Additionally, there was a significant benefit of LC on transferrin, total protein, and albumin levels of the hemodialysis patients. [12] There are also a few reports supporting the hypothesis that treatment with LC can improve chronic inflammation in hemodialysis patients. [13] Lung and kidney function are intimately related in both health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there was a significant benefit of LC on transferrin, total protein, and albumin levels of the hemodialysis patients. [12] There are also a few reports supporting the hypothesis that treatment with LC can improve chronic inflammation in hemodialysis patients. [13] Lung and kidney function are intimately related in both health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies on the effect of L-carnitine supplement on serum CRP are available, and their results are in agreement with the result of our study. 24,25 A meta-analysis on 31 prospective studies of major CVDs and nonvascular mortality showed that the hazard ratios per 100 mg/dL (or 1 g/L) increase in usual fibrinogen concentration for coronary heart disease and stroke were 2.4 and 2, respectively. 26 Therefore, the reduction of plasma fibrinogen concentration by L-carnitine supplement may play an effective role in reducing the risk of CVD and stroke in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…L-carnitine has also been reported to have anti-inflammatory characteristic in previous investigations using animal models (Winter et al, 1995;Vescovo et al, 2002;Idrovo et al, 2012;Liu et al, 2011) and human studies, including patients with type 2 diabetes mellitus (Derosa et al, 2011), nonalcoholic steatohepatitis (Malaguarnera et al, 2010), and coronary artery disease (Lee et al, 2014) and patients undergoing hemodialysis (Shakeri et al, 2010;Duranay et al, 2006;Suchitra et al, 2011). Moreover, our results demonstrated a significant difference between the treatment groups in serum level changes of MMP-3 through the study.…”
Section: Discussionmentioning
confidence: 94%